Sensitivity Limit of The VATLY Radio Telescope: Observing the Moon - Phuong, Nguyen Thi; Thao, Nguyen Thi; Darriulat, Pierre; Diep, Pham Ngoc; Hoai, Do Thi; Nhung, Pham Tuyet; Anh, Pham Tuan (Communications in Physics, 2015)
The Moon has been observed using the VATLY radio telescope at frequencies of 1420.4and 1417.6 MHz in order to study the behaviour of the instrument in a domain of ux densityclose to the limit of its sensitivity. Drift scans have revealed a Moon ux density of 0:83 0:16kJy corresponding to a Moon black body temperature of 207 40 K. From these results, a limitsensitivity of 300 Jy has been inferred in agreement with earlier coarser estimates.